2015
DOI: 10.1038/nature15698
|View full text |Cite
|
Sign up to set email alerts
|

Basomedial amygdala mediates top-down control of anxiety and fear

Abstract: Anxiety-related conditions are among the most difficult neuropsychiatric diseases to treat pharmacologically, but respond to cognitive therapies. There has therefore been interest in identifying relevant top-down pathways from cognitive control regions in medial prefrontal cortex (mPFC). Identification of such pathways could contribute to our understanding of the cognitive regulation of affect, and provide pathways for intervention. Previous studies have suggested that dorsal and ventral mPFC subregions exert … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
360
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 422 publications
(386 citation statements)
references
References 48 publications
24
360
2
Order By: Relevance
“…They used optogenetic methods to study the role of the hitherto rather neglected vmPFC-basomedial amygdala (BMA) pathway in fear conditioning and extinction (7). Their findings take us a long way from previous accounts of fear extinction and anxiety control (see sect.…”
Section: The Circuits Of Fear and Fear Extinctionmentioning
confidence: 95%
See 1 more Smart Citation
“…They used optogenetic methods to study the role of the hitherto rather neglected vmPFC-basomedial amygdala (BMA) pathway in fear conditioning and extinction (7). Their findings take us a long way from previous accounts of fear extinction and anxiety control (see sect.…”
Section: The Circuits Of Fear and Fear Extinctionmentioning
confidence: 95%
“…As the authors say, their "findings place mpITCs in a unique position to gate acquired amygdala-dependent behaviors via their direct sensory inputs" (33; see also Ref. 7). Further research on this is desirable.…”
Section: The Brain Synaptic Plasticity Processes Underlying Fear Lmentioning
confidence: 99%
“…Adhikari et al (2015) also employed this optogenetic monosynaptic connectivity method together with CLARITY and viral tracing to discover a direct connection between ventromedial prefrontal cortical (mPFC) and basomedial amygdala, which turned out to be behaviorally important for top-down regulation of fear and anxiety responses. Also studying communication between the mPFC and amygdala, Little and Carter (2013) used two-photon optogenetic methods to determine the density and distribution of amygdalar inputs onto mPFC cells, demonstrating how optogenetics can be employed for detailed functional mapping of synaptic locations.…”
Section: Functional Definition Of Circuit Elements: Wiring-dependent mentioning
confidence: 99%
“…Using (for example) fiberoptic neural interfaces, optogenetics can be used in the behavioral setting to stimulate, inhibit, or modulate a population of cell bodies within a brain region or to address a specific ODE in vivo (using either selective illumination of opsin-expressing projection terminals or the retrograde-opsin-expression strategy to recruit cells by a feature of their connectivity; Figures 3A and 3B; Deisseroth, 2014; Steinberg et al, 2015). Behavioral optogenetics experiments have demonstrated the utility of these approaches for resolving the effects of defined circuit elements; indeed, more specific behavioral effects are often observed when resolving cells by projection target instead of generally illuminating cell bodies without regard to projection target (Adhikari et al, 2015; Kim et al, 2013; Warden et al, 2012). For example, Warden et al (2012) found that optogenetic activation of prefrontal cortical projections to the dorsal raphe nucleus selectively modulated behavioral state (favoring active coping defined by motivated escape behavior in the forced swim test, while not generally increasing locomotor activity) in a manner that depended on specific activation of that pathway (in contrast, nonspecific stimulation of the prefrontal cortex or dorsal raphe, or stimulation of other projections from prefrontal cortex, did not cause the same specific effect profile).…”
Section: Functional Definition Of Circuit Elements: Wiring-dependent mentioning
confidence: 99%
“…During threat processing, the PFC is also engaged, although more gradually than the brisk response of the amygdala, which allows flexible modulation of amygdala-based processing by providing a more detailed representation of threat attributes [65,68]. Adhikari et al [69] recently reported an elegantly designed study that demonstrated that the BLA is the major target of ventral medial PFC in mice and that the BLA neurons differentiate safe and aversive environments.…”
Section: The Role Of Pka In Anxietymentioning
confidence: 99%